Optimization of Diagnostics of CSF Cycle Disorders in Children Based on Comparative Clinical and Neuroimaging Analysis (MRI and Neurosonography) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Diagnosing cerebrospinal fluid flow disorders in children, such as hydrocephalus, requires a comprehensive approach using modern neuroimaging techniques. Currently, the primary tools for assessing the condition of the brain and cerebrospinal fluid (CSF) are magnetic resonance imaging (MRI) and neurosonography (NSG). Each of these methods has its own advantages and limitations, and their complementarity allows for increased diagnostic accuracy, improved prognosis, and optimized treatment.Modern imaging techniques play an essential role for understanding the anatomy of the cerebrospinal fluid (CSF) spaces and ventricular system, as well as the hydrodynamics of CSF flow. These principles are important to the understanding of pathological processes affecting the ventricles and CSF spaces, and abnormalities induced by changes in the intracranial pressure.The classical model of CSF hydrodynamics presumes that CSF is produced primarily in the choroid plexus epithelium (and to a lesser degree in the ependymal cells) at a rate of approximately 0.2–0.6 mL/min and 400–600/day. However, numerous evidences indicate that CSF is also produced throughout the entire CSF-interstitial fluid functional unit across the walls of the central nervous system (CNS) blood capillaries [1].Since the total volume of CSF in the ventricles and subarachnoidal spaces (SAS) averages approximately 150 mL, a threefold turnover of CSF occurs daily, explaining the presence of a bulk flow of CSF from the sites of origin to the sites of absorption. This bulk flow of CSF starts in the lateral ventricles, passes through the third and fourth ventricles and, via the foramina of Luschka and the foramen of Magendie into the cerebellopontine angle and prepontine cisterns and the vallecula of the cisterna magna. From the basilar cisterns, the bulk flow of CSF continues cephalad along two major routes: a ventral route through the interpeduncular and pre-chiasmatic cisterns and a dorsomedial route through the ambient cisterns and the cisterna magna. The bulk flow also extends downward into the spinal canal dorsal to the cord to the lumbar thecal sac and upward in front of the cord to the basilar cistern.CSF is absorbed not only via the arachnoid villi that are ideally positioned to drain CSF from the SAS into the major dural sinuses, but also through the lymphatic system, and through the glymphatic system in the brain parenchyma, (extracellular fluid spaces that are in communication with the brain capillaries). In fact, it is widely accepted that the vast majority of CSF is absorbed through the capillary network of the CNS [1, 7,8].